Spaced repetition for vocabulary retention in EFL and ESL learning: A systematic literature review - Hasbuna Nikmah Shalehah; Luqman Baehaqi; M. Zaini Miftah (Universitas Islam Malang, 2026)
Vocabulary retention remains a persistent challenge among EFL and ESL learners because newly learned words are often forgotten without systematic, repeated exposure. Although spaced repetition (SR) is widely recognized as an effective strategy for long-term memory, there is still limited understanding of how SR can be optimally implemented across diverse EFL and ESL learners' contexts, particularly regarding spacing schedules, instructional design, and technology integration. As a result, evidence on SR implementation in EFL and ESL learners' vocabulary learning remains fragmented. EFL and ESL learners’ systematic literature review aims to synthesize the opportunities and challenges associated with the use of SR for vocabulary learning among EFL and ESL learners. Following the PRISMA guidelines, 25 studies published between 2010 and 2025 were selected from Scopus, Google Scholar, ScienceDirect, and ResearchGate based on predetermined inclusion and exclusion criteria. The reviewed studies examined various SR approaches, including digital flashcards, retrieval-based activities, mobile-assisted language learning applications, cumulative testing, and multimodal learning tools. The findings indicate that SR provides substantial opportunities, particularly for improving vocabulary retention and enhancing long-term memory, while also increasing learner motivation, learner autonomy, retrieval practice, and technology-enhanced language learning. However, several challenges were identified, including instructional design issues, uncertainty regarding optimal spacing schedules, technology and digital literacy constraints, learner-related differences, and limited empirical evidence across diverse educational settings. Overall, the reviewed evidence consistently points to the positive potential of SR as a cognitively efficient approach for supporting vocabulary development, particularly when implemented through well-designed instructional practices.